Documentation of Non-Timber Forest Products of Haveri District, Karnataka - Makanur, Ningaraj S.; Kotresha, K. (Indian Forester, 2025)
The present work is an inventory of non-timber forest products in Haveri District, it resulted in a total of 64 species and 56 genera, belonging to 32 families were recorded yielding 67 non-timber forest-yielding products of 8 different categories namely, Food, fodder, cosmetics, dye-yielding, handicrafts, construction materials, exudates, biodiesel and green manure yielding plants. Fabaceae is a most dominant family with the highest number of 11 species. Habit-wise analysis shown that tree species are dominant with 35 species, followed by herbs (16), shrubs (10) and climbers (3). Proper collection, processing and marketing of NTFPs provides self-employment to the people livelihoods. Conservation and management plans for sustainable utilization of these products is recommended to overcome the threat of habitat loss by anthropogenic activities.